Análisis y desarrollo de la reputación corporativa en las organizaciones modernas. Un acercamiento al estado del arte - Gómez-Bayona, Ledy (2022)
This bibliographical study explores the concept and importance of Corporate Reputation (CR) in different economic sectors and how this concept has evolved in education. Higher education institutions have been forced to implement marketing strategies that allow them to generate CR and promote the development of higher education. CR has become an object of application and practice in the academic and business worlds to achieve recognition and positioning that leads solid and lasting competitive advantages. CR in organizations and universities is explored through bibliographic research. Currently, organizations are more concerned with building a CR that can be maintained over time. This, in turn, directs institutions towards the practice of innovation and continuous development in higher education. These ideas may influence universities to begin to adopt strategic plans driven by the needs of society, especially in the context of constant global evolution.